Nutritional Therapy and Its Role in Improving the Symptoms of Polycystic Ovary Syndrome An Analytical Study (Comprehensive Journal of Science, 2026)
Polycystic Ovary Syndrome is considered one of the most common hormonal disorders affecting women of reproductive age worldwide. It is characterized by irregular ovulation, menstrual disturbances, hyperandrogenism, weight gain, acne, excessive hair growth, and infertility problems. The syndrome is also closely associated with insulin resistance, obesity, and metabolic disorders, which negatively affect women’s physical and psychological health.This research aims to highlight the role of therapeutic nutrition in improving the symptoms of Polycystic Ovary Syndrome and enhancing the overall health status of affected women. The study focuses on the relationship between dietary habits, body weight, insulin resistance, and hormonal balance, in addition to emphasizing the importance of nutritional awareness and healthy lifestyle modifications.The study also demonstrated that regular physical activity combined with therapeutic nutrition contributes to improving metabolic indicators and reducing complications such as diabetes and dyslipidemia. Furthermore, losing approximately 5–10% of body weight was associated with noticeable improvements in PCOS symptoms and The study concluded that therapeutic nutrition is one of the most effective non-pharmacological approaches for managing PCOS, due to its role in improving hormonal balance, reducing insulin resistance, and enhancing quality of life. The research recommends increasing nutritional awareness among women, encouraging healthy lifestyle practices, and strengthening the role of nutrition specialists in designing individualized dietary programs for women with PCOS.